Silences and Vulnerabilities - Suruchi Thapar-Björkert; Marion Stevens; Åsa Eriksson; Johanna Gondouin (The Thinker)
In 1999, Sweden introduced legislation that prohibits and criminalises the purchase of sex – while continuing to decriminalise the selling of sex. Referred to as the ‘Swedish model’, or the ‘Nordic model’ after neighbouring countries followed suit, this legal framework is built on an understanding of ‘prostitution’ as exploitation and a form of violence against women. Examined through this lens, the selling of sex can never be regarded as work. Through its feminist foreign policy platform (in place between 2014 and 2022), Sweden declared that it would engage in ‘persistent and robust commitment and agency’ to encourage other countries to adopt similar legal frameworks. Yet, evidence of the presumed success of the Swedish model is scant at best, with recent research raising concerns over how the Sex Purchase Act in conjunction with immigration law and third-party regulation has contributed to increased vulnerability of migrant sex workers – who make up the majority of people selling sex in the Nordic region (Vuolajärvi, 2019). In South Africa, both the selling and buying of sex is criminalised, in spite of the country being party to several international treaties that recognise the right to free choice of work. As decriminalisation of sex work in South Africa is currently high on the public agenda, and the ‘Swedish model’ is one of the alternatives discussed, critically examining the possible consequences of adopting this model is crucial. In this paper, we draw on research and activist interventions in Sweden and South Africa to examine the possible implications of the adoption of the ‘Swedish model’ in South Africa – a country with markedly different historical and demographic trajectories, migratory patterns, and a much less extensive and supported social welfare system. We caution that such a move may not achieve the aim of reducing sex workers’ vulnerability and exposure to violence. Furthermore, framing the selling of sex as violence rather than work may risk silencing causes for social justice by stripping sex workers of their agency and autonomy, while simultaneously casting them as victims.